'Ritornelos' de la memoria : lo fantástico en la narrativa de Felisberto Hernández - Quiñenao Calluil, Milla-Rhag (2016)
The purpose of this research is to study the work of Uruguayan writer Felisberto Hernández from a fantastic perspective, identifying the narrative elements used for the writer to create an uncertain-atmosphere in his stories. In the first place, the author and the felisbertians studies in general will be introduced. In the second place, theories about fantastic literature and its evolvement will be exposed - from Todorov and Bessiére to the works of Campra, Alazraki and Barrenechea-, with the aim of generate a definition of the genre for the Hispanic American Literature. With the concepts given for Campra, Alazraki and Barrenechea as background, the Hypothesis of this research is that felisbertian writing use some narrative elements to introduce an uncertainatmosphere in the stories without the need of a “breach between two worlds” commonly used by the Fantastic Literature of the XIX century. The volumes expose by this research will be Por los tiempos de Clemente Colling, work where a mature felisbertian writing is shown and that has 'the mystery' as leitmotiv of the story for the first time, and Nadie encendía las lámparas, a short-stories collection where the felisbertian writing thecnic of carrying the implicit reader to an uncertain-atmosphere is intensified.